Natural Frequency Measurement of Modest Dwelling Houses - Setiawan, Bambang; Al-Huda*, Nafisah; Yulianur, Alfiansyah; Abdullah, Nora; Juellyan, Juellyan; Permana, Athalya Khanza; Sawitri, Jihan Indria (Graduate School of Universitas Syiah Kuala, 2022)
Around 1000 to 4000 units of modest dwelling houses are annually built in Aceh Province. A modest dwelling house is a small type of house with limitations in space planning which is very suitable for small families with middle to lower incomes. This lower middle-class community is a group of people who are very vulnerable and will be very severely affected when a disaster occurs. A modest dwelling house is a one-story building with simple construction and structure in its physical form. On the other hand, Aceh is also one area that is very prone to earthquake disasters from along the subduction zone and Sumatran Fault. Therefore, measuring the frequency of a modest dwelling house is crucial to understanding all house elements' conditions. It is essential to estimate the integrity and safety of the house after an earthquake occurs. The method used in this research is using the field experiment method in the form of measuring the natural response of the building to vibration based on microtremor data. This study uses a seismometer. The data is stored in a data logger. The seismometer is placed on the floor of the house. Data collection is carried out when no major activities are around the house. Measurements were carried out for a minimum of 60 minutes. Computer analysis with specific parameters obtained using Geopsy software. The result of this study indicates that the dominant frequency of modest dwelling houses measured is around 2.99 Hz. The analysis results from the field experiment were validated using pushover analysis of the detailed engineering design data. The modeling results show that in the x-axis direction (parallel to the direction of the building), the frequency obtained is 7.14 Hz. Pushover analysis on the model with the y-axis direction (parallel to the side of the building) obtained a frequency of 7.46 Hz. This validation shows a huge difference between the frequency of field measurement results and computer modeling results. Many factors, including decreasing or degrading the concrete construction quality in the field, can cause this gap.